Environmentally sustainable color fading approaches of denim fabric using alternative garments dry process: An insight into chromatic parameters and physical properties - Rahaman, Md. Tareque; Shikder, Abdullah Al Rakib; Al Mamun, Md. Abdullah (Journal of open innovation, 2024)
Denim has been elevated to the status of "classic" in the modern fashion cycle by numerous advancements and development efforts over the past few decades. Consumers today are interested in clothing comfort, environmental sustainability, and aesthetic appeals in addition to newborn designs and novel looks. Previous research works had only focused on evaluating the physical properties of denim samples after applying existing hazardous dry processes (whiskering, sandblasting, and PP Potassium permanganate spray), but those don’t portray scientific assessment regarding environmental impact assessment, chromatic values and vintage effects of denim. This research work explores sustainable alternative dry garment processes using sodium hydroxide and heat treatment with a view to achieving highly fashionable worn-out effects on sulfur-dyed denim, focusing on color fading. Process variables such as different sodium hydroxide concentrations (5 g/L, 10 g/L, 15 g/L, and 20 g/L) and heat treatment by stenter machine operating temperatures (140°C, 160°C, 180°C, and 200 °C) are used to conducting the research. Addressing a research gap, it evaluates Environmental Impact Measurement scores using EIM Software and chromatic parameters using Datacolor Spectrophotometer. Other examining factors such as color fastness (CF), and physical characteristics such as tensile and tear strength, shrinkage%, air permeability, and contact angle are evaluated. The alternative methods of dry process using are environmentally sustainable with scores of 7 and 1 (EIM software’s scoring system implies 0–33 for low impact, 34–66 for medium impact, and >66 for high impact) respectively. Evaluations indicate decreasing patterns in color strength and chromaticity with higher sodium hydroxide concentration like 20 g/L and heat treatment, leading to a light black or grayish hue at 200°C. Conversely, lower concentrations (5 g/L, 10 g/L) and temperatures (140°C and 160°C) show increased a* (red-green), b* (yellow-blue) values, and r% (reflectance %). Fabrics treated with lower sodium hydroxide concentrations and temperatures exhibit weaker resistance to color change and staining. The study provides a comprehensive assessment using metrics like EIM score, color strength, chromaticity, hue angle, CIELAB color space, reflectance%, and color fastness tests, including rubbing, washing, and light fastness. [Display omitted] •Providing insights into how different color fading techniques impact the visual appearances of denim.•This research provides a detailed evaluation of color fading using spectrophotometry.•Focusing on growing consumer demand for sustainable fashion and style.•Emphasizing sustainable production and consumption on denim apparel.•Minimizing the major drawbacks of existing garments dry process.